Pemberdayaan Masyarakat Tiyuh Pulung Kencana, Lampung dalam Mitigasi Perubahan Iklim melalui Biopori - Pratiwi, Nadya Dwi; Putri, Sharikha Herlinanda Arya; Maria, Della; Rachma, Shafanissa Aulia; Febriani, Rossy; Adiansyah, Dias; Manurung, Patrick Marcelino; Nurhidayat, Syahrul; Sucahyo, Lilis (Jurnal Pusat Inovasi Masyarakat, 2025)
Pulung Kencana Village is one of the villages in Tulang Bawang Tengah District, West Tulang Bawang Regency, Lampung Province, which is still facing challenges in managing organic waste and drought due to climate change. Community empowerment activities in Pulung Kencana Village were carried out to increase awareness regarding climate change mitigation through biopori technology. Biopori is a simple technology that is useful for increasing water infiltration, managing organic waste, and reducing greenhouse gas emissions. The program involved some of the people of Pulung Kencana Village and students of SMKN 1 Tulang Bawang Tengah. Participants were given socialization regarding the importance of biopores in mitigating climate change, followed by a demonstration of making biopore holes. The pre-test and post-test results show an increase in public knowledge regarding biopori. This activity succeeded in creating 6 pilot biopore holes and received a positive response from the community who were interested in increasing the application of biopore technology in their area. Continuous monitoring by the community and local government support is very necessary and is expected to increase the sustainability and benefits of this program in the long term.